Investigating fetal growth restriction and perinatal risks in appropriate for gestational age infants: using cohort and within‐sibling analyses. (28th December 2018) - Cnattingius, S; Kramer, MS; Norman, M; Ludvigsson, JF; Fang, F; Lu, D
Abstract : Objective: Fetal growth restriction refers to fetuses that fail to reach their growth potential. Studies within siblings may be useful to disclose fetal growth restriction in appropriate for gestational age (AGA) infants. We analysed associations between birthweight percentiles and perinatal risks in AGA infants, using both population‐based and within‐sibling analyses. Design: Population‐based cohort study. Setting and sample: Using nation‐wide Swedish registries (1987–2012), we identified 2 134 924 singleton AGA births (10th–90th birthweight percentile for gestational age), of whom 1 377 326 were full siblings. Methods: Unconditional Poisson regression was used for population analyses, and conditional (matched) Poisson regression for within‐sibling analyses. We estimated associations between birthweight percentiles and stillbirth, neonatal mortality, and morbidity, using incidence rate ratios (IRRs) with 95% confidence intervals (CIs). Results: Stillbirth and neonatal mortality risks declined with increasing birthweight percentiles, but the declines were larger in within‐sibling analyses. Compared with the reference group (40th to <60th percentile), IRRs (95% CIs) of stillbirth for the lowest and highest percentile groups (10th to <25th and 75th–90th percentiles, respectively) were 1.87 (1.72–2.03) to 0.76 (0.68–0.85) in population analysis and 2.60 (2.27–2.98) and 0.43 (0.36–0.50) in within‐sibling analysis. Neonatal morbidity risks in term non‐malformed infants with low birthweight percentiles were generally only increased in within‐sibling analyses. Conclusion: Using birthweight information from siblings may help to define fetal growth restriction in AGA infants. Tweetable abstract: Size of siblings helps to detect growth‐restricted infants with seemingly normal birthweights. Tweetable abstract: Size of siblings helps to detect growth‐restricted infants with seemingly normal birthweights.